IMPLEMENTASI PROTOTIPE ALAT UKUR KERENTANAN LISTRIK (SUSEPTOMETER) BAHAN ANISOTROP BERBASIS KAPASITOR KEPING SEJAJAR - Yuhelsa Putra (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2015)
The prototype chip capacitor as a parallel electric field sensors and sources, as well as the operational amplifier type of instrumentation. Prototype measuring devices are capable of measuring the electric  susceptibility of dielectric material (wood and water), paraelectric (aluminum) and ferroelectric materials (iron).Voltage magnitude of the measured material processed using a graphical method to obtain the value of the gradient. From this gradient an electric susceptibility values obtained material. Measurement values  and theoretical comparison of  the results obtained  0.9 ± 0.2.  The results of  of measurements of electrical vulnerability of wood close to the value 8, while the  electric susceptibility measurement results obtained water at 81 ±2. The value of iron and   aluminum electric susceptibility values approaching infinity. Value of electric  susceptibility of these materials tend to approach the value of his theory, it is feasible prototype gauge used to measure the electric susceptibility of dielectric materials ,ferroelectric paraelectric and especially iron.